2020
DOI: 10.1186/s12935-020-01300-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-454 suppresses the proliferation and invasion of ovarian cancer by targeting E2F6

Abstract: Background: The aberrant expression of microRNA-454 (miR-454) has been confirmed to be involved in the development of cancers. However, the functional role of miR-454 in the progression of ovarian cancer remains unclear. Methods: The expression of miR-454 in ovarian cancer cells and serum of ovarian cancer patients was detected by RT-PCR. CCK8, colony formation, transwell, and flow cytometry assays were conducted to assess the effects of miR-454 on ovarian cancer cell proliferation, migration, invasion, and ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Furthermore, E2F6, a member of the nuclear transcription factor E2F family, served as a crucial mediator of miR-486-5p action in NPC. E2F6 is regulated by multiple miRNAs in human cancer ( 41 43 ), and the present study identified a similar trend for E2F6 in NPC. Notably, the final rescue experiments revealed that the modulatory activities of SLC9A3-AS1 silencing on NPC cells could be reversed by miR-486-5p downregulation or E2F6 reintroduction.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, E2F6, a member of the nuclear transcription factor E2F family, served as a crucial mediator of miR-486-5p action in NPC. E2F6 is regulated by multiple miRNAs in human cancer ( 41 43 ), and the present study identified a similar trend for E2F6 in NPC. Notably, the final rescue experiments revealed that the modulatory activities of SLC9A3-AS1 silencing on NPC cells could be reversed by miR-486-5p downregulation or E2F6 reintroduction.…”
Section: Discussionsupporting
confidence: 83%
“…After consulting the relevant documents, we found that hsa-mir-454 played a non-negligible role in the development and prognosis of multiple tumor. For example, miR-454 restrained the growth and invasion of ovarian cancer cells via regulating E2F6 (An et al, 2020). The miR-454-3p may be a meaningfully standalone prognosis marker for hepatocellular carcinoma (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, most of the miRNAs here identified as heat recorders, are related to ovarian and prostate cancer in humans, either promoting or suppressing cancer progression and thus much literature related to these diseases is available. This is the case of, for example, miR-19b [56], miR-15b [57], and miR-454 [58,59] three upregulated miRNAs in the fish ovaries after the heat and; miR-27b [60,61], miR-212 [62], miR-146b [63], and miR-34a [64], which were downregulated. The emerging research on miRNAs has flourished the utility of miRNAs as bioclinical markers in human cancers during the last decade [65,66] but also as attractive drug targets for human diseases with no current effective treatments [67,68].…”
Section: Discussionmentioning
confidence: 99%